Study of Glucose-6-Phosphate dehydrogenase activity assay in mangrove streptomyces for actinohordin and undercylprodigiosin production - Azizan, Nur Hafizah; Zainal Abidin, Zaima Azira; Sharif, Faez (Noor Publication, 2020)
This study evaluates the potential of using glucose-6-phosphate dehydrogenase activity assay for Actinohordin and Undecylprodigiosin productions from mangrove Streptomyces. Previously, there were several methods used to screen antimicrobial activities such as agar spot test and disc diffusion assay, but those are lengthy screening methods and time consuming. Thus, to overcome the limitations plate-based assay is suggested to enable rapid screening on secondary metabolite production of numerous samples at one time. The development of plate-based assay was performed by optimizing glucose-6-phosphate dehydrogenase activity assay. This coupled assay was based on the production of dihydronicotinamideadenine dinucleotide phosphate (NADPH) whereby a right combination of nicotinamide adenine dinucleotide phosphate (NADP) and glucose-6-phosphate (G6P) were refined. The production of NADPH was measured at absorbance of 340 nm where reduced cofactor NADPH are absorbed readily at this wavelength. Sample with different concentrations of crude lysate was subjected to various substrates concentration to obtain the best activity curve. Even though elucidating clear patterns is speculative, it is believed that some improvements or optimizations of this study could offer promising knowledge which can serve as useful reference in future